2009
DOI: 10.1159/000204465
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Small Bowel Injury Induced by Low-Dose Aspirin: A Crossover Study Using Capsule Endoscopy in Healthy Volunteers

Abstract: Background and Aims: Small intestinal toxicity of low-dose aspirin remains unclear. The purpose of this capsule endoscopy study was to assess the incidence of small bowel injury in healthy volunteers treated with short-term low-dose aspirin. Methods: Healthy subjects were randomly assigned to receive low-dose aspirin for 14 days (Aspirin group) or no drugs for 14 days (Control group). The two treatment occasions were separated by a washout period of at least 4 weeks. All subjects underwent capsule endoscopy at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 50 publications
2
37
0
5
Order By: Relevance
“…The reported incidence of LDA-induced small-bowel mucosal injury is 20-61.5% among healthy volunteers using short-term LDA, [24,28,29,30] and the reported prevalence of LDA-induced small-bowel mucosal injury is 42.1-100%, specifically among patients with OGIB using long-term LDA [14,24,31,32]. It is difficult to perform CE in all patients who receive NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of LDA-induced small-bowel mucosal injury is 20-61.5% among healthy volunteers using short-term LDA, [24,28,29,30] and the reported prevalence of LDA-induced small-bowel mucosal injury is 42.1-100%, specifically among patients with OGIB using long-term LDA [14,24,31,32]. It is difficult to perform CE in all patients who receive NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that low-dose aspirin is unlikely to cause significant small bowel injury [7,8]. However, several recent studies indicated that small bowel injury was caused by low-dose aspirin [22][23][24][25]. Smecol et al [24] reported increased fecal calprotectin after administration of 100 mg of aspirin for 2 weeks in 20 healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Maiden et al [25] reported gross damage in 68% of healthy volunteers taking diclofenac plus omeprazole for 2 wk. Even low-dose aspirin was found to cause significant small intestinal damage with short-term administration; thus, Endo et al [26] reported that 80% of patients taking low-dose aspirin for 2 wk had intestinal damage.…”
Section: Detection Of Nsaid-enteropathymentioning
confidence: 99%